1973
DOI: 10.1136/gut.14.6.438
|View full text |Cite
|
Sign up to set email alerts
|

Liver structure and function following small bowel resection

Abstract: SUMMARY The observation that patients with extensive small bowel resection have impaired hepatocellular function with reduced BSP clearance and fatty change in biopsies from the liver led to a systematic study of liver structure and function following proximal and distal small bowel resection in the rat.While anaesthesia and surgery impaired BSP clearance per se, small bowel resection further reduced BSP clearance with impairment of both uptake and excretion phases of BSP excretion.The increased BSP retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The association of bile salt infusion with increased hepatic secretion of BSP is well documented (O'Maille, Richards and Short, 1966;Boyer et al, 1970), and Gupta, Neale and Dowling (1973) postulated that the converse situation of a reduction in hepatic bile salt output may lead to a reduction in BSP excretion. Indeed, Mahu et al (1977) demonstrated a reduction in BSP transport in fasted rats in association with a diminished hepatic bile salt output; in these fasted rats the percentage reduction in BSP and bile salt excretion was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…The association of bile salt infusion with increased hepatic secretion of BSP is well documented (O'Maille, Richards and Short, 1966;Boyer et al, 1970), and Gupta, Neale and Dowling (1973) postulated that the converse situation of a reduction in hepatic bile salt output may lead to a reduction in BSP excretion. Indeed, Mahu et al (1977) demonstrated a reduction in BSP transport in fasted rats in association with a diminished hepatic bile salt output; in these fasted rats the percentage reduction in BSP and bile salt excretion was comparable.…”
Section: Discussionmentioning
confidence: 99%